Late remission in diabetes mellitus type 1. Presentation of a case. - Hiussymin Marchena Morera; Alina Esther González Hermida; Yanet Fragoso Cordero (Medisur)
Diabetes mellitus type I is a chronic disease in which the deficit of insulin constitutes the fundamental element; its partial or total remission is frequently close to the moment of its premiere; reports of late remission don't exist which suggest that it is less frequent. The case of a 22 years-old patient is presented, with diabetes antecedents since 2 years old whose insulin necessities progressively diminished, until the total suppression of treatment, maintaining an appropriate metabolic control, even during gestation process, which led to the total remission of the disease.